Oxygen uptake kinetics during flat and uphill cycling at high-intensity exercise in field conditions - Prinz, B.; Haselsberger, K.; Nimmerichter, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Oxygen uptake kinetics are the principal means by which the human organism generates energy to do work. Oxygen uptake kinetics are investigated by a number of studies in laboratory conditions. Few studies, however, have analysed oxygen uptake kinetics in field conditions. The aim of this study was to analyse the effect of gradient and cadence on the primary response of oxygen uptake kinetics in field conditions. Methods: Thirteen trained cyclists (mean ± SD: age 23 ± 4.7 years; stature 178.5 ± 5.2 cm; body mass 69 ± 7.8 kg; O2max 68.2 ± 4.7mL/min1/kg) performed a laboratory incremental graded exercise test (GXT) and on a separate day four 6min field-trials, two on level ground (gradient 1.5%, flat) and two uphill (gradient 5%, climb). The two trials were conducted at a cadence of 60 and 90 rev/min (rpm) and at the work rate corresponding to 70% ( 70) between the power at ventilator threshold and Pmax of the GXT. Throughout each trial gas exchange was continuously measured with a portable gas analyser (MetaMax3B, CORTEX, Germany) and power output was measured with a SRM mobile power crank (Schoberer Rad-Messtechnik, Juelich, Germany). The V O2 breath-bybreath data were interpolated at 1-second intervals and the time constant and the amplitude of the exponential primary phase were resolved by least square regression (GraphPad Prism 6.0, GraphPad Software, USA). A factorial ANOVA with cadence and inclination as model factors was used for statistical analyses. Results: The amplitude was significantly affected by cadence (F1,12 = 39.3, P < 0.001; 60 rpm: 2573 ± 53 mL, 90 rpm: 2887 ± 47 mL) but not by inclination (F1,12 = 0.002, P = 0.967; flat: 2731 ± 172 mL, climb: 2728 ± 272 mL). Time constant was not significantly affected by cadence (F1,12 = 1.7, P = 0.213; 60 rpm: 21.4 ± 2.7 sec, 90 rpm: 23.2 ± 2.2 sec) and inclination (F1,12 = 3.9, P = 0.073; flat: 24.0 ± 1.1 sec, climb: 20.5 ± 1.5 sec). The end-exercise oxygen uptake was significantly affected by cadence (F1,12 = 55.3, P < 0.001; 60 rpm: 4054 ± 125 mL, 90 rpm: 4324 ± 28 mL). No significant difference was observed between flat (4243 ± 142 mL) and uphill cycling (4134 ± 239 mL) (F1,12 = 1.5, P = 0.245). Discussion: Our findings indicate that the parameters of oxygen uptake kinetics are not influenced by inclination. This is supported by previous studies who investigated the influence of inclination in treadmill running. Based on these findings we assume that measuring the primary response of oxygen uptake kinetics is independent of inclination. However, time constant is not influenced by cadence which is in contrast to the higher amplitude and end-exercise oxygen uptake at 90 rpm.